Pengaruh Struktur Kepemilikan terhadap Pengungkapan Environmental Social Governance Perusahaan Manufaktur Terdaftar BEI (2020-2024) - Feni Refita Sari; Muslimin Muslimin (Jurnal Bisnis Inovatif dan Digital, 2026)
This study try to examine the impact of institutional, managerial, and public kepemilikan structures on the level of environmental, social, and governance (ESG) practices in manufacturing companies listed on the IDX between 2020 and 2024. This study's findings are supported by increasing transparency and business continuity, also in guiding ESG practices. The research method that is used is quantitative analysis using panel regression analysis. The study's sample consists of 27 manufacturing companies selected using the purposive sampling method, yielding a total of 135 observations over of a few years. The analysis's findings indicate that all the ownership do not significantly affect ESG. Conversely, company size and employee productivity as control variables have a positive impact on the ESG threshold. This shows the structure of kepemilikan is not the most important factor in determining ESG transparency for Indonesian manufacturing companies, which are primarily focused on the importance of jangka pendek. Implicitasi penelitian ini mengindikasi bahwa pengungkapan ESG is more negatively impacted by internal company capacity than by stock composition, therefore external regulations and technical assistance are crucial factors in guiding business operations.